Prática Avançada de Enfermagem: Perspectivas para sua implementação no Brasil - Felix, Vanessa Cappellesso Horewicz (2024)
Objective: To understand the perception of nurses, physicians, and key persons about implementing Advanced Nursing Practice (ANP) in Primary Health Care (PHC) in Brazil. Methodology: This study is part of the international multicenter project "Strengthening Advanced Nursing Practice and collaboration in Primary Health Care: a comparative study between Brazil and Germany", integrating researchers from the State University of Western Paraná (UNIOESTE), the National School of Public Health (ENSP/FIOCRUZ) and the University of Bielefeld. The focus of this research is the Brazilian scenario. It is a qualitative, descriptive, and exploratory study, carried out in a national, regional, and local setting, in the states of Paraná and Rio de Janeiro, with healthcare professionals and representatives of associations representing doctors and nurses, integrating different realities. Data was collected using an online focus group script, via the Zoom platform, and in person. The files were saved and transmitted via a password-protected folder in "sciebo", a data reservoir linked to the University of Bielefeld in Germany. All the interviews were recorded and transcribed in full using MAXQDA software, which was also used to organize the data. according to Uwe Flick, the data analysis is of the inductive thematic type. The analysis identified seven categories with their respective subcategories. For this research, the categories related to this study's objectives will be presented: interprofessional collaboration in PHC; facilitators and obstacles to the implementation of EAP in PHC; and future perspectives for EAP in PHC. Results: Doctors and nurses currently collaborate in primary care, mainly interspersing childcare, prenatal care, chronic conditions, and care for the elderly, enhancing care. However, to implement the EAP, the main problems identified were nurses' resistance due to work overload, nurses' lack of autonomy, a view of professional competition between doctors and nurses, and professional turnover. As facilitators, they highlight the importance of better knowledge of the roles of each professional; political conditions; and regulations for the implementation of the EAP, for the creation of protocols to guide and support the work, for an increase in problem solving; welcoming, and lower costs in the future. However, it is a process that needs to be discussed. Final considerations: There are activities that nurses and doctors carry out that correspond to EAP, but for it to be implemented, it is necessary to broaden professionals' understanding of this practice and provide conditions for its effective exercise, to enable better results in health conditions for the population.